2019
DOI: 10.1264/jsme2.me19067
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stage-dependent Bacterial Communities in Soybean Plant Tissues: <i>Methylorubrum</i> Transiently Dominated in the Flowering Stage of the Soybean Shoot

Abstract: Plant-associated bacteria are critical for plant growth and health. However, the effects of plant growth stages on the bacterial community remain unclear. Analyses of the microbiome associated with field-grown soybean revealed a marked shift in the bacterial community during the growth stages. The relative abundance of Methylorubrum in the leaf and stem increased from 0.2% to more than 45%, but decreased to approximately 15%, with a peak at the flowering stage at which nitrogen metabolism changed in the soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
(61 reference statements)
4
14
0
Order By: Relevance
“…Disruption of genes responsible for synthesis of specialized metabolites such as triterpenes, sesterterpenes, and coumarins in Arabidopsis revealed the functions of these metabolites in modulating microbial communities (Chen et al, 2019;Huang et al, 2019;Stringlis et al, 2018;Voges, Bai, Schulze-Lefert, & Sattely, 2019). In soybean, changes in rhizosphere microbial communities during development and continuous cropping have been analyzed (Hara, Matsuda, & Minamisawa, 2019;Liu, Hewezi et al, 2019;Liu, Pan et al, 2019;Sugiyama, Ueda, Zushi, Takase, & Yazaki, 2014). We recently reported that daidzein, the major isoflavone secreted from soybean roots, diffuses within a few millimeters from the root surface and shapes the soybean rhizosphere bacterial communities (Okutani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of genes responsible for synthesis of specialized metabolites such as triterpenes, sesterterpenes, and coumarins in Arabidopsis revealed the functions of these metabolites in modulating microbial communities (Chen et al, 2019;Huang et al, 2019;Stringlis et al, 2018;Voges, Bai, Schulze-Lefert, & Sattely, 2019). In soybean, changes in rhizosphere microbial communities during development and continuous cropping have been analyzed (Hara, Matsuda, & Minamisawa, 2019;Liu, Hewezi et al, 2019;Liu, Pan et al, 2019;Sugiyama, Ueda, Zushi, Takase, & Yazaki, 2014). We recently reported that daidzein, the major isoflavone secreted from soybean roots, diffuses within a few millimeters from the root surface and shapes the soybean rhizosphere bacterial communities (Okutani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2019 ). Moreover, recent time-series physiological studies in various plant species have demonstrated that longer physiological responses often depend on genetic variations, as well as on plant age and stage ( Hara et al. 2019 , Ohnishi et al.…”
Section: Assessing Plant–environment Interactions Over Timementioning
confidence: 99%
“…Data on nif gene expression and nitrogenase activity in non-legume diazotrophs have provided a snapshot of different plant contexts such as plant growth stage [20] and circadian rhythm [111] under fluctuations of carbon supply from plants. Time series analysis based on the development of sequence technologies [112,113,114] would reveal the dynamics of truly functional diazotrophs in plant tissues and rhizosphere.…”
Section: Research Perspectivesmentioning
confidence: 99%